Numerical simulation of the effect of irrigation method on soil water movement in greenhouse - SHEN Ming-wei; HAO Fei-lin (浙江大学学报. 农业与生命科学版)
In greenhouse crop production, water required is supplied mainly through drip and spray irrigation. Based on Navier-Stockes equation, the Computational Fluid Dynamics (CFD) software CFX was adopted to simulate the soil water movement under conditions of different irrigation methods. The rate of water supply was set at the same level. The result shows that the way of irrigation had an important effect on soil water movement and distribution. In the case of drip irrigation, soil water mostly concentrates in the rhizosphere of the crop, where the water utilization efficiency was relatively high. The form of water contacted area approximated sphericity and the shape of the sphere tended to blur and stretch to the deep soil layer in the increaing time of continued irrigation. In the case of spray irrigation, soil water infiltrated from one layer to another, the water content in each soil layer was basically similar. Water was evenly distributed and the water would occupy much less soil volume at the same rate of irrigation, and more water was needed to meet the crop water requirement compared with drip irrigation.